2016
DOI: 10.1007/s12020-016-1173-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation vs. microwave ablation for patients with benign thyroid nodules: a propensity score matching study

Abstract: With well-matched groups and consistent procedure design, our results demonstrated that the volume reduction ratio, therapeutic success rate, symptom and cosmetic score, and complications related to treatment for the two techniques are equivalent. Radiofrequency ablation and microwave ablation are both effective and safe methods in treating benign thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 32 publications
6
55
1
2
Order By: Relevance
“…MWA was also associated with a slightly higher complication rate than RFA (7 vs. 5%, respective-ly) [81]. These results have been confirmed by a retrospective study of 108 patients after propensity score adjustment [82].…”
Section: Comparison Of Outcomes Of Different Ta Techniques For Benignmentioning
confidence: 77%
“…MWA was also associated with a slightly higher complication rate than RFA (7 vs. 5%, respective-ly) [81]. These results have been confirmed by a retrospective study of 108 patients after propensity score adjustment [82].…”
Section: Comparison Of Outcomes Of Different Ta Techniques For Benignmentioning
confidence: 77%
“…Voice change is usually transient, and most patients recover spontaneously within 3 months without special treatments. [819212641424346] Prednisone may be useful for reducing the recovery period. [22] One patient experienced permanent right paramedian vocal cord palsy with inspiratory stridor but without dysphonia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent retrospective study 16 concluded that the VRRs achieved by RFA and MWA for the treatment of BTNs at 1, 3, 6 and 12 months follow-up were no statistical significance. To compare with the results of our study, except the influence of the number of the enrolled patients, a low microwave power output of 20-35 W might contribute to minimize the carbonization in the ablated nodules and increase the VRR of MWA group at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…MWA seems to be a safe and effective technique for the treatment of BTNs 15 . A recent interesting study 16 retrospectively compared the clinical outcomes of RFA and MWA and concluded that both of them were effective and safe methods in treating BTNs. The purpose of the present prospective multicenter study was to further evaluate the clinical outcomes of the two techniques.…”
mentioning
confidence: 99%